Willingness to Fight for Chile as an Effect of Social Representations of the War of the Pacific and the Mediating Role of Identity Fusion in Secondary School Students - Hatibovic, Fuad Juso (2023)
This article examines the impact of social representations of the War of the Pacific and identity fusion on the willingness to fight for Chile among high school students. A correlational design was used. The participants were 116 Chilean high school students with an average age of 16.76 years (SD = .73). Correlation analyses show that there is an association between identity fusion, social representations of the War of the Pacific, and willingness to fight for Chile. People with higher identity fusion are more willing to defend the national ingroup. Mediation analyses showed that the mediating variables, namely identity fusion, explain the relationship between social representations of the War of the Pacific and the criterion variable.